2000
DOI: 10.1038/sj.jp.7200358
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Velocity Changes After Bovine Natural Surfactant Instillation

Abstract: OBJECTIVE:To determine the effects of bovine natural surfactant (beractant) instillation on cerebral hemodynamics in preterm infants with respiratory distress syndrome (RDS). STUDY DESIGN:Preterm infants who required surfactant for RDS were enrolled. Cerebral blood flow velocity (CBFV) waveforms from the pericallosal artery were analyzed by pulsed Doppler ultrasonography with the anterior fontanel serving as an acoustic window. CBFV was measured before and at 5, 10, 20, and 30 minutes after the first dose of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…8,9 Differences in surfactant preparations, volume and timing of administration probably explain the widely different cerebral blood flow responses to surfactant. Previous studies reported that cerebral blood flow decreased, 10-13 increased 9,14 -18 and remained unchanged [19][20][21][22][23][24] following various surfactant preparations, administered under varying conditions. Thus, as with the cerebral circulation, we believe that the differential pulmonary effects of beractant and poractant alfa may be responsible for indirect effects on PDAs and PDA hemodynamics.…”
Section: Discussionmentioning
confidence: 95%
“…8,9 Differences in surfactant preparations, volume and timing of administration probably explain the widely different cerebral blood flow responses to surfactant. Previous studies reported that cerebral blood flow decreased, 10-13 increased 9,14 -18 and remained unchanged [19][20][21][22][23][24] following various surfactant preparations, administered under varying conditions. Thus, as with the cerebral circulation, we believe that the differential pulmonary effects of beractant and poractant alfa may be responsible for indirect effects on PDAs and PDA hemodynamics.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies examining the effects of natural bovine surfactant on cerebral hemodynamics 8,9 used intermittent monitoring protocols and failed to find any study sample changes in CBFv, PaCO 2 , and MABP, although some individuals had changes in CBFv during surfactant administration. The discrepancy between these studies and ours may be due to aggressive ventilator management after surfactant instillation, the lower dose volume (1.1 mL/kg) used by Jorch et al, 8 and intermittent monitoring in which transient changes could have been overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances of arterial blood gases (ABGs) after surfactant also may have deleterious effects on CBF, since carbon dioxide and oxygen are potent mediators of cerebral vascular tone. 7 Studies of the acute effects of surfactant on cerebral hemodynamics have reported decreased, 2 unchanged, 5,8,9 or increased 3,4 CBF variables. Discrepancies in these results may be due to use of different surfactant preparations, differences in administration protocols, use of diverse CBF measurement techniques and indirect ABG measures, intermittent physiologic monitoring, and inclusion of heterogeneous populations.…”
mentioning
confidence: 99%
“…However, results from experimental and clinical trials are equivocal: Decrease of arterial blood pressure resulted in a consecutive drop of CBFV in three studies [4, 31,36], in another study CBFV increased as a result of increased blood pressure and increase of pO 2 [41]. Rey and colleagues found a decrease of CBFV without a change of mean arterial blood pressure [33].…”
Section: Hemodynamic Effects and Cerebral Perfusionmentioning
confidence: 99%